Circular Economy Philosophy Based on Hifz al-Bi'ah for Economic Justice - Prima Dwi Priyatno; Ahmad Hasan Ridwan; Nurrohman Syarif (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
This study develops a comprehensive conceptual framework that integrates the principle of al-‘adl (economic justice) within the circular economy (CE), moderated by Hifz al-Bi'ah (environmental protection) based on Maqasid Shariah, to create a just and sustainable economy. The research uses a qualitative-conceptual method, combining a systematic literature review and thematic synthesis to analyze how Islamic principles can be integrated into CE practices. The findings indicate that incorporating al-‘adl and Hifz al-Bi'ah into CE practices helps to achieve equitable resource distribution, protect vulnerable groups, and ensure intergenerational justice. This integration also promotes ethical governance and accountability in resource management, ensuring that economic activities contribute not only to immediate economic growth but also to long-term environmental and social sustainability. Furthermore, this approach aligns with the objectives of Maqasid Shariah, particularly in safeguarding public welfare (maslahah ‘ammah) and ensuring that environmental stewardship is prioritized. By combining these principles with circular economy practices like eco-design, zero waste, and circular supply chains, the study highlights the potential for creating a more inclusive and sustainable development model that reflects Islamic values of justice, moderation, and ecological balance. Penelitian ini mengembangkan kerangka konsep yang mengintegrasikan prinsip al-‘adl (keadilan ekonomi) dalam ekonomi sirkular (CE), dimoderasi oleh Hifz al-Bi'ah (perlindungan lingkungan) berdasarkan Maqasid Shariah, untuk menciptakan ekonomi yang berkeadilan dan berkelanjutan. Penelitian ini menggunakan metode kualitatif-konseptual, yang menggabungkan tinjauan pustaka sistematis dan sintesis tematik untuk menganalisis bagaimana prinsip-prinsip Islam dapat diintegrasikan ke dalam praktik-praktik CE. Hasil penelitian menunjukkan bahwa pengintegrasian al-‘adl dan Hifz al-Bi'ah dalam praktik CE membantu mewujudkan distribusi sumber daya yang adil, melindungi kelompok rentan, dan memastikan keadilan antargenerasi. Integrasi ini juga mendorong tata kelola yang etis dan akuntabilitas dalam pengelolaan sumber daya, memastikan bahwa aktivitas ekonomi tidak hanya berkontribusi pada pertumbuhan ekonomi jangka pendek tetapi juga pada keberlanjutan sosial dan lingkungan jangka panjang. Selain itu, pendekatan ini sejalan dengan tujuan Maqasid Shariah, terutama dalam melindungi kesejahteraan publik (maslahah ‘ammah) dan memastikan bahwa perlindungan lingkungan menjadi prioritas. Dengan menggabungkan prinsip-prinsip ini dengan praktik ekonomi sirkular seperti eco-design, zero waste, dan rantai pasokan sirkular, penelitian ini menunjukkan potensi untuk menciptakan model pembangunan yang lebih inklusif dan berkelanjutan yang mencerminkan nilai-nilai Islam tentang keadilan, moderasi, dan keseimbangan ekologis.